Gestão do capital intelectual e as bibliotecas universitárias - Torino, Emanuelle (2008)
The growing competition stimulates organizations to invest in something that provides them with very competitive advantages. Through this, it is possible to verify that the contained knowledge in the organizations' human resources is the unique belonging capable of assuring them a good position into the market. The relationship between organization and its staff, when viewed through the optics of knowledge, becomes clearer. Due to this, it is noticeable the need for investment in learning, once knowledge is the only one active which remains powerful when all the rest is in crisis. The organization that really invests in learning and knowledge generation, that values its intellectual capital, owns a great differential in the face of competition once these actives, which constitute the intellectual capital, determine either the success or failure of an organization. In this sense, this work is inserted in the context of university libraries and aims to approach the importance of attributing value to the intellectual capital of their managers.